MacroH2A histone variants limit chromatin plasticity through two distinct mechanisms. (3rd September 2018) - Kozlowski, Marek; Corujo, David; Hothorn, Michael; Guberovic, Iva; Mandemaker, Imke K; Blessing, Charlotte; Sporn, Judith; Gutierrez‐Triana, Arturo; Smith, Rebecca; Portmann, Thomas; Treier, Mathias; Scheffzek, Klaus; et al.
Abstract: MacroH2A histone variants suppress tumor progression and act as epigenetic barriers to induced pluripotency. How they impart their influence on chromatin plasticity is not well understood. Here, we analyze how the different domains of macroH2A proteins contribute to chromatin structure and dynamics. By solving the crystal structure of the macrodomain of human macroH2A2 at 1.7 Å, we find that its putative binding pocket exhibits marked structural differences compared with the macroH2A1.1 isoform, rendering macroH2A2 unable to bind ADP‐ribose. Quantitative binding assays show that this specificity is conserved among vertebrate macroH2A isoforms. We further find that macroH2A histones reduce the transient, PARP1‐dependent chromatin relaxation that occurs in living cells upon DNA damage through two distinct mechanisms. First, macroH2A1.1 mediates an isoform‐specific effect through its ability to suppress PARP1 activity. Second, the unstructured linker region exerts an additional repressive effect that is common to all macroH2A proteins. In the absence of DNA damage, the macroH2A linker is also sufficient for rescuing heterochromatin architecture in cells deficient for macroH2A. Synopsis: MacroH2A histones limit chromatin dynamics through two mechanisms: macroH2A linker‐mediated chromatin stability and macroH2A1.1 isoform‐mediated PARP inhibition. The structure of the macrodomain of macroH2A2 is incompatible with nucleotide binding. MacroH2A1.1 binds ADP‐ribose and inhibits PARP1‐dependent DNA‐damage induced chromatin dynamics. The unstructured basic linker region of all macroH2A histones is sufficient to restrain chromatin expansion after acute DNA damage and stabilizes heterochromatic structures. Abstract : MacroH2A histones limit chromatin dynamics through two mechanisms: macroH2A linker‐mediated chromatin stability and macroH2A1.1 isoform‐mediated PARP inhibition.